Perancangan Platform MOOC Di Kota Jambi Dengan Fitur Video Live Streaming - Hendri Hendri (Jurnal Processor, 2022)
In the current covid 19 pandemic, where a lot of business businesses are experiencing difficulties, including course institutions and tutoring. Many tutoring teachers have been sent home. Online Tutoring platforms such as Ruangguru are very popular with the public. The purpose of this research is to create a MOOC Massively Open Online Course platform which is an important innovation in the world of education. By using the live streaming feature, it allows students to learn directly with tutoring teachers directly. Massively Open Online Course/ MOOC provides a way for more independent education. This MOOC is very good if applied in Jambi city which has a limited number of teachers.